How to ‘deconvolute’ lung evolution - evolutionary lessons from cell culture - Torday, John S. (Henry Stewart Talks, 2016)
Tissue interactions during morphogenesis, Automaturation due to mechanotransduction, PTHrP is stretch-regulated, Dissociation of endoderm from mesoderm and fibrosis, Co-culture of endoderm and mesoderm lead to homeostasis, Neutral Lipid Trafficking